LEGAL CERTAINTY REGARDING THE IMPOSITION OF CRIMINAL EXTORTION SANCTIONS INVOLVING COMMUNITY ORGANIZATIONS (ORMAS) - Susanto, Heri; Sinaulan, Ramlani Lina; Ismed, Mohamad (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
The purpose of this study is to examine the legal certainty afforded to community organizations that commit extortion, as well as to analyze and propose criminal punishments against community organizations that commit extortion. The method utilized in this study is normative legal research, which is conducted in order to elicit the relevant data for the topic. The data used are secondary data and tertiary legal materials. The data analysis was conducted utilizing a qualitative method of legal analysis. According to the findings of this study, the government must be resolute in enforcing the law against a person who is a member and/or administrator of a community organization and who intentionally and directly or indirectly violates the provisions, including extortion, violence, and disturbing the peace and order. destroying public and social facilities, committing acts of hostility against ethnicity, religion, race, or class; engaging in separatist activities that jeopardize the Unitary State of the Republic of Indonesia's sovereignty; and adhering to, developing, and spreading teachings or understandings contrary to Pancasila. To ensure legal certainty for a person acting in conformity with existing legal provisions, Community Organizations are not an exception; on the contrary, Community Organizations lack legal certainty. Articles of extortion and threats as defined in Article 368 paragraph (1) of the Criminal Code (KUHP) criminal sanctions imposed on individual Ormas who commit the extortion crime specified in Article 368 of the Criminal Code still do not satisfy the community's sense of justice because the threats are only 9 (nine) years in prison, with no fines or other additional penalties to the organization concerned.